(untitled) (Research, Society and Development, 2016)
Assistive technology is considered a field of Special Education for studying different types of technological resources and adapted to the inclusion of persons with disabilities in the educational and social context. The aim of this study was to identify, through the Assistive Technology (TA), the possibilities of communication and education of students with cerebral palsy. The methodology used was a brief literature review. specifically discussed the use of alternative communication, one of the types of Assistive Technology in the service of students Cerebral Palsy. We have seen that these students in particular can benefit from the use of Alternative Communication, to improve and / or expand their communication, getting through it, communicate, relate and be included in the social educational context. Therefore, this study is relevant to the academic world, it brings contributions to disseminate knowledge about the Assistive Technology: alternative communication as one more possibility of inclusion of people with cerebral palsy in society, thus ensuring equality of opportunities.